The Influence of Location, Price, and Facility on Interest in Revisiting Wego Lamongan Tourism : Case Study on Gondang Outbond Lamongan Educational Tourism - Puguh Cahyono; Nur Laili (RTTM, 2024)
According to Rahmawati (2016:3) it is stated that marketing is one of the activities that aims to identify or explain and find human needs, while marketing management itself according to Agustina Shinta (2011:2) marketing management is an effort to plan, implement (which consists of an activity of organizing, directing, and coordinating) as well as supervising and or controlling marketing activities in an organization in order to achieve the organization's goals effectively and efficiently. The population of this study is visitors at WEGO which amounted to 13,257 from the number that the author got from the management of Gondang Outbond Educational Tourism and calculated by the slovin formula, the sample result was 100 people. The analysis model used in this study is multiple linear regression. Based on the results of the regression test, a value of Y of -0.470 + 0.342X^1 + 0.722X^2 + 0.118X^3, From this value it can be concluded that the most dominant factor for the bound variable (Interest in Returning Visits) is Price because it has the highest beta value of 0.554.